Flypaper Effect Pada Belanja Daerah Kabupaten/ Kota Di Provinsi Sumatera Selatan Tahun 2018-2022 - Cahyani, Vira Mustika; Firmansyah, Firmansyah; Dwitayanti, Yevi (Politeknik Negeri Ambon, 2025)
The study is to examine the effect of General Allocation Funds (DAU) and Regional Original Income (PAD) on Regional Expenditure and to see if there is a flypaper effect of District/ City on Sumatera Selatan Province in 2018- 2022. The population is LRA in 17 districts/cities and 85 observation units. The data in this study were tested by descriptive statistics, classic assumption test, coefficient of determination, t-value test, F-test, and flypaper effect detection on regional expenditure, which were processed using Statistical Package for the Social Application Sciences (SPSS) version 26. The result states that the independent variables significantly positively affect variable dependent Keywords: General Allocation Funds, Regional Original Income, Regional Expenditure, and Flypaper Effect.